Characterizing Employees' Preferences for Incentives for Healthy Behaviors: Examples to Improve Interest in Wellness Programs. Issue 6 (November 2019) - Jenkins, Kristi Rahrig; Fakhoury, Nour; Richardson, Caroline R.; Segar, Michelle; Krupka, Erin; Kullgren, Jeffrey
Background . Many employers now incentivize employees to engage in wellness programs, yet few studies have examined differences in preferences for incentivizing participation in healthy behaviors and wellness programs. Method . We surveyed 2, 436 employees of a large university about their preferences for incentivizing participation in different types of healthy behaviors and then used multivariable logistic regression to estimate associations between employees' socioeconomic and demographic characteristics and their preferences for incentives for engaging in healthy behaviors. Results. Compared with nonunion members, union members had higher odds of wanting an incentive for eating healthily (adjusted odds ratio [AOR] = 1.60, 95% [CI; 1.21, 2.12]), managing weight (AOR = 1.53, 95% CI [1.14, 2.06]), avoiding drinking too much alcohol (AOR = 1.41, 95% CI [1.11, 1.78]), quitting tobacco (AOR = 1.37, 95% CI [1.06, 1.77]), managing stress (AOR = 1.37, 95% CI [1.08, 1.75]), and managing back pain (AOR = 1.64, 95% CI [1.28, 2.10]). Compared with staff, faculty employees reported higher odds for wanting an incentive for reducing alcohol intake (AOR = 1.34, 95% CI [1.00, 1.78]) and quitting tobacco (AOR = 1.43, 95% CI [1.04, 1.96]). Women had lower odds than men (AOR = 0.80, 95% CI [0.64, 0.99]) of wanting an incentive for managing back pain. Conclusions. Preferences for incentives to engage in different types of healthy behaviors differed by employees' socioeconomic and demographic characteristics. Organizations may consider using survey data on employee preferences for incentives to more effectively engage higher risk populations in wellness programs.